2007
DOI: 10.1088/0031-9155/52/13/007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of system geometry and other physical factors on photon sensitivity of high-resolution positron emission tomography

Abstract: We are studying two new detector technologies that directly measure the three-dimensional coordinates of 511 keV photon interactions for high-resolution positron emission tomography (PET) systems designed for small animal and breast imaging. These detectors are based on (1) lutetium oxyorthosilicate (LSO) scintillation crystal arrays coupled to position-sensitive avalanche photodiodes (PSAPD) and (2) cadmium zinc telluride (CZT). The detectors have excellent measured 511 keV photon energy resolutions ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 54 publications
1
67
0
3
Order By: Relevance
“…To provide sufficient DoI information and increase intrinsic spatial resolution, successive generations of PET scanners have tended to reduce the size of the scintillation crystals-or, in the extreme case, may eliminate the scintillator altogether, instead using direct gamma photon detection in pixellated semiconductor detector arrays (typically fabricated from relatively thick silicon or CZT) (Domenico et al 2007, Habte et al 2007, Park et al 2007, Li et al 2013. This geometry results in a very large number of potential LoRs, especially for 3D scanners with a multi-ring geometry.…”
Section: Introductionmentioning
confidence: 99%
“…To provide sufficient DoI information and increase intrinsic spatial resolution, successive generations of PET scanners have tended to reduce the size of the scintillation crystals-or, in the extreme case, may eliminate the scintillator altogether, instead using direct gamma photon detection in pixellated semiconductor detector arrays (typically fabricated from relatively thick silicon or CZT) (Domenico et al 2007, Habte et al 2007, Park et al 2007, Li et al 2013. This geometry results in a very large number of potential LoRs, especially for 3D scanners with a multi-ring geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The detector modules can be tightly stacked to maximize packing fraction, and their ability to position the 3-D coordinates of individual photon interactions enables uniform spatial resolution throughout the system's 8 cm x 8 cm x 8 cm field of view [1,4]. The modules are arranged such that annihilation photons enter the CZT crystal edge-on to traverse a minimum of 4 cm of CZT material, yielding >86% intrinsic detection efficiency for single 511 keY photons (>73% for coincident pairs) [2,3]. MIlL's prior studies of CZT focused on the performance of singular CZT crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for determining DoI include placing photodetectors on opposite sides of a single scintillator slab and using the relative pulse heights to determine DoI (phoswitch detector), using a non-uniform optical coupling between adjacent pairs of scintillator crystals, in which DoI is determined from the relationship between the energies measured in the adjacent crystals, and segmenting (optically isolating) the scintillator and detectors in the radial direction [2], [3], [4]. Simulation based studies have also suggested alternative system geometries such as box-like formation (as apposed to cylendrical) to optimise photon sensitivity [5].…”
Section: Introductionmentioning
confidence: 99%